OSTEOGENIC MANIPULATION OF HUMAN WHARTONâS JELLY-DERIVED MESENCHYMAL STEM CELLS USING COMPOSITE SCAFFOLD FROM POLY(?-CAPROLACTONE) AND BIOSILICA SPONGE XESTOSPONGIA TESTUDINARIA - Ardiyansyah, Andika
Bone defects are conditions where bones cannot function normally due to trauma such as accidents, microorganism infections, and the ageing process. To date, the treatment of bone defects in Indonesia still relies on conventional methods, namely bone grafting. In bone grafting, the damaged area is transplanted with bone from the patient or a donor. The main limitation of this method is the limited supply of transplants, leading to the development of bone tissue engineering as an alternative therapy involving three main components: cells, scaffolds, and bioactive factors. In this study, human Wharton’s jelly-derived mesenchymal stem cells (hWJ-MSCs) were used due to their multipotent properties, allowing them to differentiate into osteoblasts through mechanical and chemical induction by a composite scaffold containing biosilica from the sponge Xestospongia testudinaria. The research aimed to determine the biosilica concentration with the best material characteristics, biocompatibility, and osteoinductivity as a biomaterial for the scaffold to support the proliferation and differentiation of hWJ-MSCs into osteoblasts. The composite scaffold was fabricated using the salt leaching method and consisted of four treatments: pure PCL as a negative control and PCL with biosilica concentrations of 20%, 30%, and 50%. The results showed that the composite scaffold with 50% biosilica concentration exhibited the best material characteristics, biocompatibility, and osteoinductivity compared to other treatments. Based on material characteristics, the presence of silica (SiO2) functional groups was identified using FTIR; the scaffold withstood up to 90% damage under a pressure of 316.564 MPa; a contact angle test result of 73.698° ± 0.256°; and a water uptake of 75.6% ± 1.25%, characterising the 50% biosilica scaffold as hydrophilic. Biocompatibility was demonstrated by observing the morphology of hWJ-MSCs adhering to the scaffold surface using SEM and MTT cytotoxicity tests on day 3, as well as MTT proliferation tests up to day 14, marked by an increase in cell viability to 148.25% ± 1.96%. Osteoinductivity was tested using immunocytochemistry (ICC) and Alizarin Red on day 21, with the successful differentiation process marked by the observation of osteogenic markers at the osteoblast stage, namely osteopontin (OPN) and collagen type-1 (COL1) using confocal microscopy, as well as mineral deposition with an OD value of 0.317 ± 0.034 for Alizarin Red. The results indicate that increasing the biosilica concentration in the scaffold can enhance cell adhesion, proliferation, differentiation, and mineralisation, suggesting that biosilica-containing scaffolds can be developed for bone tissue engineering in the future.